Impact of forestry operations on forest soil respiration depending on stands features in Kastamonu, Turkiye - Genc, Cigdem Ozer; Aricak, Burak (Univ Federal Lavras-Ufla, 2025)
Background: Harvesting, especially skidding operations have a significant impact on the forest soil properties. This study aimed to advance understanding of how timber harvesting may influence soil respiration in forested ecosystems. We investigated the impact of soil respiration for some of the skidding techniques after skidding operations depending on slope and stand types. Results: We measured soil CO2 efflux to evaluate the skidding techniques on soil, depending on the slope and stand type. Thus, three skidding techniques with tractor for harvesting (1-suspended skidding, 2-using a skidding cone, 3-cable-pulling) were used in 6 different study site and the variations in soil respiration and soil properties were examined at 3 different slopes (0-20%, 20-33%, >33%), 2 different stand types (b-bc, c-cd) at topsoil (0-5 cm). Also soil respiration was measured at intervals of 5 days (on days 1, 5, and 10) after skidding operation. In addition, pH, EC (electrical conductivity), and soil moisture were evaluated depending on slope and stand type in the study. Conclusion: It was determined that respiration increased on the first day but decreased on day 5 and 10. It was found that the slope and stand type have no effect on soil respiration. It was determined that the skidding technique that reduces the soil respiration the most is suspended skidding with a rate of 90%. However, the skidding technique that reduced respiration the least was skidding by using a skidding cone suspended skidding with a rate of 64% when evaluated on day 10.
Keywords: Skidding operations; Skidding techniques; Forest soil respiration; Pinus nigra